How just is transportation justice theory? The issues of paternalism and production. (April 2019) - Vanoutrive, Thomas; Cooper, Erin
Highlights: Karel Martens' theory of transportation justice is a valuable contribution. Seeing transit as a compensation for the poor can be stigmatizing. It is not clear why self-financing in transportation should be the norm. Justice is not only about distribution, but also about the production of services. Abstract: The topic of justice has increasingly attracted attention from transportation scholars, and a variety of perspectives and approaches are employed to study this topic. Arguably the most elaborate and sophisticated theory is put forward by Karel Martens in his 2017 book "Transport justice". We start with a critical reading of Karel Martens' work which is based on the work of liberal philosophers such as Richard Dworkin. While Martens makes several telling points, we explore how debates in the justice literature apply to the case of transportation, and may question aspects of transportation justice theory. In particular we discuss the issues of (1) the paternalistic treatment of people below the accessibility poverty line, and (2) the production and planning of transportation services. Two cases are used to inform this theoretical discussion, on the one hand, the Transportation Justice movement in California, and on the other, the "basic accessibility" debate in Flanders (Belgium).